Unveiling the intricate interplay: Exploring biological bridges between renal ischemia-reperfusion injury and T cell-mediated immune rejection in kidney transplantation. - Xinyi Xia; Xinrui Fan; Shan Jiang; Yuhan Liao; Yang Sun (PLoS ONE)
Although the link between ischemia-reperfusion injury (IRI) and T cell-mediated rejection (TCMR) in kidney transplantation (KT) is well known, the mechanism remains unclear. We investigated essential genes and biological processes involved in interactions between IRI and TCMR. Methods Renal IRI and TCMR datasets were obtained from the Gene Expression Omnibus database. IRI and TCMR co-expression networks were built using weighted gene co-expression network analysis, and essential modules were identified to acquire shared genes and conduct functional enrichment analysis. Shared genes were used for TCMR consensus clustering, differentially expressed genes (DEGs) were identified, and gene set enrichment analysis (GSEA) was conducted. Three machine learning algorithms screened for hub genes, which underwent miRNA prediction and transcription factor analysis. Hub gene expression was verified, and survival analysis was performed using Kaplan-Meier curves. Results IRI and TCMR shared 84 genes. Functional enrichment analysis revealed that inflammation played a significant role. Based on shared genes, TCMR was divided into two clusters. GSEA revealed that graft rejection-related pathways varied between the two clusters. TCMR hub genes, guanylate-binding protein 1 (GBP1) and CD69, showed increased expression. Decreased survival rates were found in patients who had undergone KT and had high GBP1 and CD69 levels. Conclusions The study demonstrates that renal IRI has a potential role in renal TCMR and the pathogenic pathways are potentially inflammation-related.